Aptasensing of ciprofloxacin residue using graphene oxide modified with gold nanoparticles and branched polyethyleneimine. Issue 46 (17th October 2022) - Mahmoudpour, Mansour; Nazhad Dolatabadi, Jafar Ezzati; Hasanzadeh, Mohammad; Rad, Aziz Homayouni; Torbati, Mohammadali; Seidi, Farzad
Abstract : A convenient platform was fabricated for the electrochemical assay of ciprofloxacin using aminated aptamer immobilized in GO-PEI-AuNPs nanocomposite. Abstract : Precise monitoring of antibiotic residues in aqueous solution is of vital significance for safeguarding the environment and food resources. Herein, a convenient platform was fabricated for the electrochemical assay of ciprofloxacin (CFX) in real milk samples using aminated aptamer and graphene oxide nanogold-functionalized branched polyethyleneimine (GO-PEI-AuNPs) nanocomposite. For the first time, a gold electrode was modified with GO-PEI-AuNPs. The modified surface endowed excellent electrochemical substrates with large surface areas, excellent electron transfer rates, and suitable capabilities to firmly attach high amounts of aptamer. After further modification of substrate with CFX specific aptamer a recognition probe enabling selective and sensitive determination of CFX was realized. All of the aptasensor fabrication steps were surveyed via cyclic voltammetry techniques. The construction and morphology of the GO-PEI-AuNPs composite were evaluated by UV-Vis spectroscopy, transmission electron microscopy, and field emission scanning electron microscopy. Under optimal conditions, the suggested scaffold can offer an acceptable linear range of 0.001 to 100 μM and a low limit of quantification of 0.001 μM for selective and sensitive monitoring of CFX in real samples. The effectiveness of the apta-assay was confirmed by detection of CFX in pasteurized and local milk samples for which suitable analytical results were achieved. It is expected that the developed substrate can be facilely extended to other aptamer-based multiplex screening platforms in actual food and environmental samples.